Smart Personality Development Model in Software Developer - Kartika Ayuningtiyas; Suryanto Suryanto; Nuri Herachwati (Research Synergy Foundation, 2023)
In this Industry 4.0 era, digital facilities are used by companies from all fields. In this digitalization development era, there are more software development companies established to offer software development services. It makes software developers an increasingly popular job today. In order to get qualified software developers, companies need to identify the smart personality of software developers. Smart personality is very useful for knowing the company’s needs in determining the criteria for prospective software developers. This research aims to analyze the development of smart personality in software developers. Data in this research were obtained using the descriptive qualitative research method and through in-depth interviews. The data collected were analyzed by thematic analysis in accordance with the results of interviews. Based on the results, it can be concluded that a software developer with smart personality has the following characteristics: they do not have to be good looking, they have to be well-skilled in their field, have strong/good logic, have good analysis skill, and can do coding neatly and carefully. The main smart personality types that can make a software developer good are they have to be well-skilled in their field, have strong/good logic and have good analysis skill.